Mini-Percutaneous Nephrolithotomy With an Endoscopic Surgical Monitoring System for the Management of Renal Stones: A Retrospective Evaluation - Gui, Huiming; Wang, Hanzhang; Kaushik, Dharam; Rodriguez, Ronald; Wang, Zhiping (Frontiers in Surgery, 2022)
Purpose: To compare the outcomes and postoperative quality of life of patients with renal calculi who underwent standard percutaneous nephrolithotomy (sPNL), mini-invasive percutaneous nephrolithotomy (mPNL) or mPNL with an endoscopic surgical monitoring system (ESMS) using a retrospective clinical trial. Methods: Eighty-six adult patients with renal stones who were treated with sPNL were retrospectively compared to ninety-two patients who were treated with mPNL between July 2014 and December 2017. Next, further studies were retrospectively conducted using a matched paired method. The ninety-two patients treated with mPNL were divided into two groups based on whether the endoscopic surgical monitoring system (ESMS) was used (ESMS-mPNL vs. non-ESMS-mPNL). The ESMS used strain gauge transducers to measure the inflow and outflow of irrigation solution. Bleeding and fluid absorption during endoscopic surgery could be accurately calculated by computer program in ESMS. Results: The fluoroscopy time, complication rate, stone-free status and clinically insignificant residual fragment (CIRF) rate were not significantly different between the two groups (sPNL vs. mPNL). The mPNL group had a significantly longer operation time than the sPNL group, and the mPNL group exhibited a markedly reduced 12-h postoperative visual analogue pain scale (VAS) score, mean hospitalization time, and return to work time, had slightly reduced haemoglobin loss, and underwent more tubeless operations. Moreover, among the 92 patients who underwent mPNL, the operation time (P = 0.090), complication rate (P = 0.996), stone-free status (P = 0.731), CIRF rates (P = 0.125) and number of tubeless operations (P = 0.760) were not significantly different between the two subgroups (non-ESMS-mPNL vs. ESMS-mPNL); however, the patients in the ESMS-mPNL group had significantly longer operation times than those in the non-ESMS-mPNL subgroup, along with marked reductions in irrigation fluid absorption, blood loss, haemoglobin loss, 12 h postoperative VAS score, mean hospitalization time, and return to work time. Conclusions: We think that ESMS-mPNL is less painful for patients and more efficacious than non-ESMS-mPNL, and ESMS-mPNL achieves a stone-free rate that is similar to non-ESMS-mPNL in patients receiving treatment for 20–40 mm kidney stones.